THE NEOLOGISM ГЕЈМИНГ (GAMING) IN THE MACEDONIAN LANGUAGE - Janusheva, Violeta (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2025)
Considering the researcher’s experience, the word’s appearance, and its exclusion from the latest dictionary, this study discusses the new word гејминг (gaming) in the Macedonian language, in relation to its emergence, word formation productivity, transfer to the general language, and current status. The aim is to obtain profound data on this neologism’s nature and to showcase its orthographical implications. The sample consists of 950 internet sources related to information technology (IT), obtained by Google search on the keyword гејминг, and the analysis exploits the qualitative content analysis based on coding and the interpretative-inductive method. The results indicate that since its appearance in 2009, it continues to be present mostly in the specialized IT lexicon among experts in this field. Further, besides the word’s formation capacities, given its exclusion from the latest Macedonian dictionary and the existence of the domestic synonym, it seems reasonable to assume that the Macedonian language has no need for its adaptation. Furthermore, it is more likely that the domestic word играње will transfer from the general lexicon into the specialized game language. Finally, the results confirm that each neologism has its path in a given language and should be approached as a separate language unit.